Crystal structural analysis of human serum albumin complexed with hemin and fatty acid - Zunszain, Patricia A (BioMed Central, 2003)
BACKGROUND: Human serum albumin (HSA) is an abundant plasma protein that binds a wide variety of hydrophobic ligands including fatty acids, bilirubin, thyroxine and hemin. Although HSA-heme complexes do not bind oxygen reversibly, it may be possible to develop modified HSA proteins or heme groups that will confer this ability on the complex. RESULTS: We present here the crystal structure of a ternary HSA-hemin-myristate complex, formed at a 1:1:4 molar ratio, that contains a single hemin group bound to subdomain IB and myristate bound at six sites. The complex displays a conformation that is intermediate between defatted HSA and HSA-fatty acid complexes; this is likely to be due to low myristate occupancy in the fatty acid binding sites that drive the conformational change. The hemin group is bound within a narrow D-shaped hydrophobic cavity which usually accommodates fatty acid; the hemin propionate groups are coordinated by a triad of basic residues at the pocket entrance. The iron atom in the centre of the hemin is coordinated by Tyr161. CONCLUSION: The structure of the HSA-hemin-myristate complex (PDB ID 1o9x) reveals the key polar and hydrophobic interactions that determine the hemin-binding specificity of HSA. The details of the hemin-binding environment of HSA provide a structural foundation for efforts to modify the protein and/or the heme molecule in order to engineer complexes that have favourable oxygen-binding properties.